Insulin resistance and hyperandrogenemia independently predict nonalcoholic fatty liver disease in women with polycystic ovary syndrome. Issue 2 (March 2019) - Harsha Varma, Sree; Tirupati, Sunanda; Pradeep, T.V.S.; Sarathi, Vijaya; Kumar, Dileep
Abstract: Aims: To find the prevalence and predictors of nonalcoholic fatty liver disease (NAFLD) in Asian Indian polycystic ovary syndrome (PCOS) women. Materials and methods: This is a prospective, cross-sectional study conducted at a tertiary care hospital from South India. Sixty women fulfilling the Rotterdam (2003) criteria for PCOS were recruited for the study. All participants were evaluated with ultrasound abdomen for fatty liver and additional biochemical investigations including fasting plasma glucose, postprandial plasma glucose, serum insulin, lipid profile and liver function tests. Results: The mean age of the study population was 24.06 ± 5.9 (range: 15–39) years. Oligomenorrhea, hirsutism and acne were present in 58 (96.7%), 37 (61.7%) and 33 (55%) women. Mean BMI of the study population was 29.5 ± 5.28 (range: 19.95 to 45.44) kg/m 2 . Fifty (83.3%) women were obese (BMI: ≥ 25 kg/m 2 ). Twenty-three (38.3%) women with PCOS had NAFLD. Three women each had isolated elevation of alanine transaminase (ALT) and aspartate transaminases (AST) whereas three women had elevation of both. All women with elevated transaminases had NAFLD. By univariate analysis, factors associated with NAFLD were serum total cholesterol, serum insulin, HOMA-IR, hyperandrogenism, ALT and AST. On multiple regression analysis using linear regression, HOMA-IR and hyperandrogenemia were the only significant predictors of NAFLD. Conclusion: Our study reports NAFLD in more than one third of Asian Indian women with PCOS. In addition to insulin resistance (HOMA-IR), hyperandrogenemia is an independent predictor of NAFLD in women with PCOS.